Optimization and application of 5G bearer network backhaul bandwidth estimation model - Yang YE; Huiting FANG; Dantong NIE (Dianxin kexue)
In the early stage of 5G construction,business requirements are unclear,technology maturity needs to be improved,and traffic growth methods are unpredictable.How to evaluate the capacity of the existing network bearer system according to different construction scenarios and choose a reasonable 5G bearer network construction plan problem.Through theoretical research on the typical configuration of the 5G single base station bearer bandwidth demand assessment method,combined with the engineering experience of 4G network construction,the national sampling survey data was used to demonstrate the huge gap between the theoretical bandwidth estimation model and the actual traffic level.The initial planning and construction of the 5G bearer network was scientifically guided,and an optimized model for the estimation of the 5G bearer network backhaul bandwidth was proposed,and its application in the evolution path of the new 5G bearer network through new scenarios,expansion,and upgrade value was illustrated.